A Comprehensive Review on Function of miR-15b-5p in Malignant and Non-Malignant Disorders - Ghafouri-Fard, Soudeh; Khoshbakht, Tayyebeh; Hussen, Bashdar Mahmud; Jamal, Hazha Hadayat; Taheri, Mohammad; Hajiesmaeili, Mohammadreza (Frontiers in Oncology, 2022)
miR-15b-5p is encoded by MIR15B gene. This gene is located on cytogenetic band 3q25.33. This miRNA participates in the pathogenesis of several cancers as well as non-malignant conditions, such as abdominal aortic aneurysm, Alzheimer's and Parkinson’s diseases, cerebral ischemia reperfusion injury, coronary artery disease, dexamethasone induced steatosis, diabetic complications and doxorubicin-induced cardiotoxicity. In malignant conditions, both oncogenic and tumor suppressor impacts have been described for miR-15b-5p. Dysregulation of miR-15b-5p in clinical samples has been associated with poor outcome in different kinds of cancers. In this review, we discuss the role of miR-15b-5p in malignant and non-malignant conditions.